O-glycosylation of Fibrinogen from Different Mammalian Species as Revealed by the Binding of Escherichia coli Biotinylated Lectins - L’Hôte, Corine; Berger, Sylvie; Karamanos, Yannis (Thrombosis and Haemostasis, 1996)
After the demonstration that neither N-glycans nor neuraminic acid are involved in the binding of K88 lectins to the Bp and y chains of porcine fibrinogen and that their recognition was due to O-glycans (L’Hôte C, Berger S, Bourgerie S, Duval-Iflah Y, Julien R, Karamanos Y. Infect Immun 1995; 63: 1927-1932) it clearly appeared that these lectins could be used as probes to detect O-glycans on fibrinogens of other species. The conclusion of the present study is that many mammalian fibrinogens contain complex O-glycans on βp and γ chains. In addition, the combined use of the biotinylated K99 lectin and the Peanut agglutinin demonstrated the presence of sialylated T-antigens on the A± chains of all the fibrinogens examined. These lectins can now be used to determine differences on the glycosylation status of fibrinogens within one species and also to detect O-glycans on other glycoproteins